Peranan Wilayathul Hisbah dalam Meminimalisir Pelaku Khalwat di Kabupaten Aceh Tengah The Role Of Wilayathul Hisbah In Minimizing The Civilizers In The Central Aceh District - Syahputra Syahputra; Abdul Kadir; Muhammad Aswin Hasibuan (Perspektif: Jurnal Ilmu-ilmu Sosial)
Aceh is the first entry point of Islam in Southeast Asia, precisely in Peurlak East Aceh on 1 Muharram 225 Hijrah. The term "Serambi Mekkah" as a predicate given to the Nanggroe Aceh Darussalam (NAD) region shows that Aceh is very strong with Islamic tradition. The results showed that in the implementation of duties  and  functions  Wilayathul  Hisbah  has  been  optimal  in  carrying out  its function, especially in minimizing the perpetrators of khalwat in Central Aceh district. In view of the data Year 2014 s / d Year 2015 Continue to progress in minimizing the perpetrators of the khalwat which signifies Wilayathul Hisbah Institution has been optimal in carrying out its duties and functions, but there are still some obstacles faced by Wilayathul Hisbah institutions are: 1. In an effort to enforce Islamic Shariah Wilayathul Hisbah institutions still face various perceptions that are less good. 2. Lack of public role in the enforcement of Islamic Sharia especially Khalwat 3. Lack of budget Oprasional and Infrastructure.